Evaluating the impact of the project implementation profile (PIP) tool on interface management in public sector projects: case study KZN Department of Health Facilities - Dube, Ndabezinhle (Department of Construction Economics and Management, 2017)
Purpose: The research study investigated the impact of the Project Implementation Profile (PIP) tool on Interface Management (IM) in Public sector facilities projects focusing on KZN Department of Health as a case study. The study identified the interface management challenges encountered by the department and also the advantages that can be realised in using the PIP tool. Lastly the study outlined the impact the PIP tool can bring in improving interface management between stakeholders. Design and Findings: From the existing literature the interface challenges were categorized as financial, contract and specification, environmental and lastly other common problems. The research determined their relevance through a survey. Respondents listed additional challenges and highlighted the advantages and impact of the PIP tool in mitigating interface challenges during project implementation. Practical Implications: The findings outlined the interface management challenges, the advantages of using the PIP tool to mitigate the challenges and the impact the tool has in improving project success rate. However constraints were encountered as some stakeholders were skeptical in answering all the questions. Subjectivity of the information couldn't be avoided as respondents were giving their opinions. It is suggested that this research be expanded in scope to verify that the findings can be generalized. Background: KwaZulu Natal Department of Health (KZNDOH) experience Interface Management challenges in implementation of its infrastructure projects. This has lead scope creeps, time and cost overruns thereby reducing the project success rate. The PIP tool could be the answer in resolving challenges faced. Aim: The research intention is to establish the impact of the PIP tool when applied to the IM with the purpose of improving the probability of project success in KZNDOH. Methods: A Likert Scale questionnaire was used to establish the current IM challenges. This was coupled with an Action Research method establish additional challenges, the impact of the PIP tool and its advantages. Results: The research delineated IM challenges which reduce the project success rate. It also outlined the impact of the PIP tool which includes improved planning, monitoring and execution of projects. Conclusions: The PIP has a positive impact to the IM challenges as established by the research. Risks are mitigated early during planning, teamwork, efficiency is improved and scope is managed. There is reduction in time and cost overruns resulting in improved project success rate.